Early magnetic resonance imaging control after temporomandibular joint arthrocentesis - Ângelo, DF (2015)
Temporomandibular joint (TMJ) lysis and lavage arthrocentesis with viscosupplementation are an effective treatment for acute disc displacement (DD) without reduction. Clinical success seems to be related to multiple factors despite the lack of understanding of its mechanisms. The authors present a case report of 17-year-old women with acute open mouth limitation (12 mm), right TMJ pain-8/10 visual analog scale, right deviation when opening her mouth. The clinical and magnetic resonance imaging (MRI) diagnosis was acute DD without reduction of right TMJ. Right TMJ arthrocentesis was purposed to the patient with lysis, lavage, and viscosupplementation of the upper joint space. After 5 days, a new MRI was performed to confirm upper joint space distension and disc position. Clinical improvement was obtained 5 days and 1 month after arthrocentesis. Upper joint space increased 6 mm and the disc remained displaced. We report the first early TMJ MRI image postoperative, with measurable upper joint space.